Pengaruh Kompetensi Sumber Daya Manusia, Perangkat Pendukung, Sistem Pengendalian Intern, dan Dukungan Organisasional terhadap Keberhasilan Penerapan Standar Akuntansi Pemerintah Berbasis Akrual: Studi Empiris Organisasi Perangkat Daerah Kabupaten Klaten - Suci Nastiti Salsabila; Nashirotun Nisa Nurharjanti (LPPM Universitas Putera Batam, 2022)
This study aims to determine the effect of Human Resource Competence, Supporting Devices, Internal Control Systems and Organizational Support on the Successful Implementation of Accrual-Based Government Accounting Standards. The approach used in this research is a quantitative approach. This research was conducted on 20 Regional Apparatus Organizations (OPD) of Klaten Regency. The number of samples taken was 85 employees. This research uses purposive sampling. Data collected by the questionnaire method. Data analysis using Multiple Regression Analysis which includes descriptive statistics, classical assumption test, and hypothesis testing (multiple linear regression, simultaneous test, and partial test). Based on the test results in this study, it can be said that the competence of human resources and internal control systems affect the successful application of accrual-based government accounting standards. Meanwhile, supporting tools and organizational support have no effect on the success of implementing accrual-based government accounting standards